Evaluation of the impact of non-slip socks on the motor recovery of elderly people in acute care hospitals: Protocol for a randomized, controlled trial study. - Thomas Rulleau; Lucie Planche; Agnès Dorion; Girolamo Soldani; Cécile Blain; Catherine Chapeleau; Yves Bleher; Cécile Da Silva; Nathalie Launeau; Emmanuelle Joguet; Ronan Fevrier; Romain Decours (PLoS ONE, 2023)
Background Older patients often arrive in acute care wards with inappropriate footwear. Hospitals may provide non-slip socks to improve the patients' safety. However, few studies have been conducted on the benefits of non-slip socks. A recent literature review found only two randomized controlled studies that evaluated non-slip socks, but the socks were not the primary focus of the studies. The aim of this study is therefore to specifically evaluate the benefits of non-slip socks on gait in hospitalized older people. Methods This open, randomized, controlled trial will include patients aged 75 years and over, hospitalized in an acute medical unit. Patients will be randomized to either remain barefoot or wear non-slip socks throughout their stay. The primary outcome is gait speed, assessed on Day 1 and Day 8. Discussion This randomized controlled trial should provide clinicians with a scientific rational for the recommendation, or not, of the use of non-slip socks for older patients in acute care hospitals. Trial registration https://clinicaltrials.gov/ on May 12, 2021 under the reference: NCT04882696 https://clinicaltrials.gov/ct2/show/NCT04882696.